Glaucoma Detection Using CNN - K.N. Brahmaji Rao; G. Sai Yugandhar; P. Girish (International Journal of Advanced Robotics and Automation Technology, 2024)
The word “glaucoma” refers to both the progressive loss of retinal cells within optic nerve, and the gradual loss of vision caused by optic neuropathy. A condition that affects eye vision is called glaucoma. This condition is thought to be permanent and causes visual impairment. There are no early warning signs of this glaucoma in them. The effect is so subtle that we could not even observe that your vision has changed. Today, several models have been created to accurately detect glaucoma. Thus, we describe an architecture built on deep learning and convolutional neural network for enhanced glaucoma detection. CNN can be used to differentiate among the patterns created for glaucoma and non-glaucoma. This Glaucoma Detection Web Application, patients' retinal pictures are given and it detects the glaucoma significance and provide the results
Keywords: Convolutional neural network; Deep Learning; Glaucoma; Optic neuropathy; Retinal cells; Visual deterioration